Gonadal function after busulfan compared with treosulfan in children and adolescents undergoing allogeneic hematopoietic stem cell transplant - Faraci, Maura; Dreger, Peter (Biology of blood and marrow transplantation, 2019)
Gonadal impairment is an important late effect with a significant impact on quality of life of transplanted patients. The aim of this study was to compare gonadal function after busulfan (Bu) or treosulfan (Treo) conditioning regimens in pre- and postpubertal children. This retrospective, multicenter study included children transplanted in pediatric European Society for Blood and Marrow Transplantation (EBMT) centers between 1992 and 2012 who did not receive gonadotoxic chemoradiotherapy before the transplant. We evaluated 137 patients transplanted in 25 pediatric EBMT centers. Median age at transplant was 11.04 years (range, 5 to 18); 89 patients were boys and 48 girls. Eighty-nine patients were prepubertal at transplant and 48 postpubertal. One hundred eighteen children received Bu and 19 Treo. A higher proportion of girls treated with Treo in the prepubertal stage reached spontaneous puberty compared with those treated with Bu (P=.02). Spontaneous menarche was more frequent after Treo than after Bu (P < .001). Postpubertal boys and girls treated with Treo had significantly lower luteinizing hormone levels (P=.03 and P=.04, respectively) compared with the Bu group. Frequency of gonadal damage associated with Treo was significantly lower than that observed after Bu. These results need to be confirmed in a larger population.